Multi-objective optimization of pultruded composite sandwich panels for building floor rehabilitation - Garrido, Mário (2019)
Composite sandwich panels are being increasingly considered for civil engineering structural applications, offering high versatility in constituent materials and their geometrical arrangement. This translates to a high number of design variables, in addition to a potentially large number of design requirements and objectives related to the panels' functions. This paper presents an optimization study of a composite sandwich panel system for building floor rehabilitation, using the Direct MultiSearch (DMS) method. Pultruded multicellular panels with a polyurethane (PUR) foam core and carbon- or glass-fibre reinforced polymer (C/GFRPF) faces and ribs/webs are considered. The panel architecture was defined using 3 geometrical variables and 14 material related variables. In addition, 8 competing objective functions were studied, related to aspects such as structural serviceability and resistance, thermal insulation, acoustic performance, cost minimization, and environmental performance. The results are presented in the form of Pareto optimal sets, from which several conclusions are drawn regarding common design-related options. The influence of core material density, of the number of ribs/webs, or of the type of fibre reinforcement and its respective layup on the different objective functions are addressed. Optimal solutions for meeting different design purposes are presented, providing useful insights for structural designers and sandwich panel manufacturers.